Facing The Challenges of Youth Moral Degradation In The Digital Age - M. Imamul Muttaqin; M. Imron Fasichullisan; Najmi Nahdin Afkari; Salsa Amanda Sabella; Siti Habibah Azzahro; Siti Latifatus Sholikhah (MA'ALIM: Jurnal Pendidikan Islam, 2023)
In this digital era, technological developments are developing very rapidly. People find it very easy to get the things they like, so negative and positive effects appear. Seeing these developments can have negative impacts that are no less than positive ones. The generation that is vulnerable to negative influences is youth and results in moral degradation. This very rapid technological development can trigger loopholes to do things that harm other people and things that are criminal. This moral degradation is very difficult if you only rely on certain theories. In Islam there are teachings of aqidah morals which are expected to be able to provide solutions to the problem of moral degradation. This strategy can be in the form of an understanding of adolescents about moral beliefs and guidance in solving self-problems.